2022
DOI: 10.1093/plcell/koac348
|View full text |Cite
|
Sign up to set email alerts
|

Producing fast and active Rubisco in tobacco to enhance photosynthesis

Abstract: Ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) performs most of the carbon fixation on Earth. However, plant Rubisco is an intrinsically inefficient enzyme given its low carboxylation rate, representing a major limitation to photosynthesis. Replacing endogenous plant Rubisco with a faster Rubisco is anticipated to enhance crop photosynthesis and productivity. However, the requirement of chaperones for Rubisco expression and assembly has obstructed the efficient production of functional foreign Rubis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…At 1% CO 2 , the transgenic plants showed a slower growth rate than WT plants (Fig. 4 c, d ) and the Hn Rubisco-expressing tobacco plants 44 . We note that although the production of CB Tob did not cause marked effects on the chloroplast ultrastructure (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…At 1% CO 2 , the transgenic plants showed a slower growth rate than WT plants (Fig. 4 c, d ) and the Hn Rubisco-expressing tobacco plants 44 . We note that although the production of CB Tob did not cause marked effects on the chloroplast ultrastructure (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Quantification of the Rubisco content, by examining the regression of Rubisco activity against the concentration of the Rubisco inhibitor carboxyarabinitol-1,5-bisphosphate (CABP) 48 , further revealed that the Rubisco content in the transgenic chloroplasts was ~30% the Nt Rubisco content in WT tobacco chloroplasts (Table 1 and Supplementary Fig. 1 ) and slightly less than that in the Hn Rubisco-expressing tobacco chloroplasts; 44 however, this value is greater than the Rubisco content in transgenic tobacco chloroplasts that produce simplified cyanobacterial α-carboxysomes (~10% the Nt Rubisco level in WT chloroplasts) 38 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, several metabolites have been produced by transferring entire biosynthetic pathways into plastids (Fuentes et al, 2018; Jensen and Scharff, 2019). Additionally, transferring the carbon-concentrating mechanism (CCM) from cyanobacterium into plastids to improve photosynthesis illustrates ways in which agronomic traits can be modified by plastid engineering (Lin et al, 2014; Long et al, 2018; Chen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%